2019
DOI: 10.1063/1.5131447
|View full text |Cite
|
Sign up to set email alerts
|

Anodic decomposition of surface films on high voltage spinel surfaces—Density function theory and experimental study

Abstract: Oxidative decomposition of organic-solvent-based liquid electrolytes at cathode material interfaces has been identified as a main reason for rapid capacity fade in high-voltage lithium ion batteries. The evolution of "cathode electrolyte interphase" (CEI) films, partly or completely consisting of electrolyte decomposition products, has also recently been demonstrated to be correlated with battery cycling behavior at high potentials. Using Density Functional Theory (DFT) calculations, the hybrid PBE0 functional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(48 citation statements)
references
References 103 publications
4
44
0
Order By: Relevance
“…The EC molecule decomposes at 4 ps, and a total of six oxygen atoms are lost on the surface at 30 ps. The EC molecule undergoes successive dehydrogenation (2.246 ps) and ring-opening (3.546 ps) reactions before decomposition, in accordance with the results of previous work. , Figures S2 and S3 show how the EC molecule gradually loses electrons before decomposition along with these reactions. At 2–2.245 ps, the EC molecule, especially the oxygen atom on the carbonyl group (noted as O­(C)), gradually approaches the top surface of the slab and electrons are transferred to the surface via O­(C).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The EC molecule decomposes at 4 ps, and a total of six oxygen atoms are lost on the surface at 30 ps. The EC molecule undergoes successive dehydrogenation (2.246 ps) and ring-opening (3.546 ps) reactions before decomposition, in accordance with the results of previous work. , Figures S2 and S3 show how the EC molecule gradually loses electrons before decomposition along with these reactions. At 2–2.245 ps, the EC molecule, especially the oxygen atom on the carbonyl group (noted as O­(C)), gradually approaches the top surface of the slab and electrons are transferred to the surface via O­(C).…”
Section: Resultssupporting
confidence: 89%
“…32−35 In the subsequent process, EC molecules may be decomposed into CO, CO 2 , and other fragments. 32,36,37 (3) Mn dissolution: Although the calculation models are not exactly the same, the conclusions that surface hydroxyl groups (H atoms from EC or other solvents) and surface oxygen vacancies will weaken the binding of Mn to the substrate and promote Mn dissolution are consistent, 38−40 and it is also confirmed that the presence of F − will further promote Mn dissolution. 38−40 And in the previous work, we proposed that the dissolution of Mn is the result of interface evolution.…”
Section: ■ Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…While rechargeable batteries are revolutionizing the way we consume energy, challenges remain to advancing the electrolytes at their center. The large number of electrolyte mixtures and materials investigated evidences the challenge in balancing their conductivity between the electrodes with their electrochemical stability at the electrode surface. , Nonaqueous liquid electrolytes, in particular, have dominated the advancement of the lithium-ion chemistry that has successfully powered personal electronics and reimagined car engines. , Consistent focus has been placed on optimizing the material properties of the electrolytes (e.g., salt solubility, viscosity, ionic conductivity) comprised of linear and cyclic carbonates mixed with lithium salts. However, the importance of the surface chemistry between the electrolyte and the electrodes has complicated the search for new materials, particularly for high-voltage applications. …”
Section: Introductionmentioning
confidence: 99%
“…This has prevented the development of guidelines for the combined use of strain and nonstoichiometry to tune the redox chemistry of metal-oxide surfaces and/or promote the emergence of bespoke electronic and magnetic surface properties. This situation is particularly unfortunate for LIBs, where control of the reactions at the electrode/electrolyte interface is essential for the stability of electrode–electrolyte interphases, namely the solid-electrolyte interphase (SEI) at the anode, and the cathode electrolyte interphase (CEI) at the cathode, that are critical for the performance and lifetime of devices. Such a knowledge gap also prevents rational, expedited progress in the fields of oxide-based photo-electro-catalysis, ,, oxide-based sustainable spintronics, and, critical for the present study, at the interface between these areas of research and their focus on different chemical and physical properties of the same (or compositionally similar) oxides.…”
Section: Introductionmentioning
confidence: 99%